Thermal clothing to reduce heart failure morbidity during winter: a randomised controlled trial. Issue 10 (8th October 2017) - Barnett, Adrian Gerard; Stewart, Ian; Beevers, Andrea; Fraser, John F; Platts, David
Abstract : Objective: To examine whether providing thermal clothing improved the health of patients with heart failure during winter. Design: Parallel group randomised controlled trial. Setting: Large public hospital in Brisbane during winter 2016. Participants: 91 patients with systolic or diastolic heart failure who were over 50 years old. Intervention: 47 patients were randomised to receive thermal clothes (socks, top and hat) and 44 received usual care. Patients could not be blinded to their randomised group. All patients' data were available for the primary outcome which was collected blind to randomised group. Main outcome measures: The primary outcome was the mean number of days in hospital during winter. Secondary outcomes included quality of life and sleep, and blood tests were collected for cardiovascular risk factors. Participants completed clothing diaries in midwinter which were used to estimate their overall clothing insulation using the 'clo'. Monitors inside the participants' homes recorded indoor temperatures throughout winter. Results: The mean number of days in hospital during winter was 4.2 in the usual care group and 3.0 in the thermal clothing group (mean difference –1.2 days, 95% CI –4.8 to 2.5 days). Most participants (85%) in the thermal clothing group reported using the thermals. There was an increase in overall clothing insulation at night in the thermal clothing group (mean difference 0.13 clo, 95% CI 0.03 to 0.23). Most participants in both groups did not wear sufficient clothing (defined as a clo below 1) and regularly experienced indoor temperatures below 18°C during midwinter. Conclusions: There was no clear statistical improvement in health in the thermal clothing group. Efforts to improve health during winter may need to focus on passive interventions such as home insulation rather than interventions that target behaviour change. Trial registration number: ACTRN12615001023549; Results .